Qavāʻid-i Mīr : Malikushshuʻarā Ḥaz̤rat Mīr Taqī Mīr Dihlavī ke sīnah basīnah Urdū zabān ke mustanad qāʻide - ʻIshrat, Ḵẖvājah Muḥammad ʻAbdurraʼūf (SAMP early 20th-century Indian books project, 1919)
On the poetry of Mīr Taqī Mīr, d. 1810.